The biostimulation of anaerobic digestion with (semi)conductive ferric oxides: their potential for enhanced biomethanation - Baek, Gahyun; Kim, Jaai; Cho, Kyungjin; Bae, Hyokwan; Lee, Changsoo (Springer Verlag, 2015)
The effect of biostimulation with ferric oxides, semiconductive ferric oxyhydroxide, and conductive magnetite on the anaerobic digestion of dairy wastewater was examined in a batch mode. The reactors supplemented with ferric oxyhydroxide (R2) and magnetite (R3) showed significantly enhanced biomethanation performance compared with the control (R1). The removal of chemical oxygen demand (COD) after 30 days was 31.9, 59.3, and 82.5 % in R1, R2, and R3, respectively. The consumed COD was almost fully recovered as biogas in R2 and R3, while only 79 % was recovered in R1. The total energy production as biogas was accordingly 32.2, 71.0, and 97.7 kJ in R1, R2, and R3, respectively. The reactors also differed in the acid formation profile with more propionate and butyrate found in R1 and more acetate found in R3. The enhanced biomethanation seems to be associated with variations in the bacterial community structure supposedly induced by the ferric oxides added. In contrast, no evident variation was observed in the archaeal community structure among the reactors. The potential electric syntrophy formed between Methanosaeta concilii-like methanogens and electroactive iron-reducing bacteria, particularly Trichococcus, was likely responsible for the enhanced performance. The stimulated growth of fermentative iron reducers may also have contributed by altering the metabolic characteristics of the bacterial communities to produce more favorable acidogenic products for methanogenesis. The overall results suggest the potential of biostimulation with (semi)conductive ferric oxides to enhance the rate and efficiency of the biomethanation of organic wastes. This seems to be potentially attractive, as increasing attention is being paid to the energy self-sufficiency of waste/wastewater treatment processes today.